2021
DOI: 10.1371/journal.pmed.1003620
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA dynamics and recurrence risk in patients undergoing curative intent resection of colorectal cancer liver metastases: A prospective cohort study

Abstract: Background In patients with resectable colorectal liver metastases (CRLM), the role of pre- and postoperative systemic therapy continues to be debated. Previous studies have shown that circulating tumor DNA (ctDNA) analysis, as a marker of minimal residual disease, is a powerful prognostic factor in patients with nonmetastatic colorectal cancer (CRC). Serial analysis of ctDNA in patients with resectable CRLM could inform the optimal use of perioperative chemotherapy. Here, we performed a validation study to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
122
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 25 publications
14
122
4
Order By: Relevance
“…In patients with resectable colorectal liver metastases (CRLMs), ctDNA was detectable in 46/54 (85%) patients prior to any treatment. In this group a median 40.93-fold decrease in ctDNA MAF with neoadjuvant chemotherapy was observed, although ctDNA clearance during neoadjuvant chemotherapy was not associated with a better RFS [ 97 ]. Notably, those with postoperative ctDNA-positivity had a significantly lower RFS (HR 6.3, 95% confidence interval or CI 2.58–15.2, p < 0.001) and OS (HR 4.2, 95% CI 1.5–11.8, p < 0.001) compared to patients with undetectable postoperative ctDNA, suggesting a role in guiding adjuvant therapy decisions in this arena.…”
Section: Prediction Of Response To Systemic and Surgical Therapies In Metastatic Colorectal Cancermentioning
confidence: 99%
“…In patients with resectable colorectal liver metastases (CRLMs), ctDNA was detectable in 46/54 (85%) patients prior to any treatment. In this group a median 40.93-fold decrease in ctDNA MAF with neoadjuvant chemotherapy was observed, although ctDNA clearance during neoadjuvant chemotherapy was not associated with a better RFS [ 97 ]. Notably, those with postoperative ctDNA-positivity had a significantly lower RFS (HR 6.3, 95% confidence interval or CI 2.58–15.2, p < 0.001) and OS (HR 4.2, 95% CI 1.5–11.8, p < 0.001) compared to patients with undetectable postoperative ctDNA, suggesting a role in guiding adjuvant therapy decisions in this arena.…”
Section: Prediction Of Response To Systemic and Surgical Therapies In Metastatic Colorectal Cancermentioning
confidence: 99%
“…In such cases, noninvasive liquid biopsy can be a potent option for treatment. It has been reported that the recurrence rate after surgery is higher when mutations are detected in ctDNA after surgery [ 12 ]. For example, the presence of minimal residual disease (MRD) may be a factor for determining the need for more intensive anticancer drug treatment after surgery.…”
Section: Liquid-based Cgp Panelmentioning
confidence: 99%
“…Both Yaqi Wang and Pradeep Chauhan and their respective colleagues evaluate ctDNA as a tool capable of predicting complete pathological response (pCR) in locally advanced rectal cancer (LARC) and muscle invasive bladder cancer (MIBC), respectively [ 1 , 2 ]. Jeanne Tie and colleagues focus on ctDNA evaluation in high-risk metastatic colorectal cancer with liver metastases (CRLM), both during neoadjuvant therapy and following surgery and adjuvant therapy [ 3 ]. In this brief perspective we evaluate these advances within the wider context of recently published work.…”
Section: Introductionmentioning
confidence: 99%